Guidelines for Community Development Worker Performing Duties in Changing Situations - Chinnawong, Pongsatorn; Siriwong, Phitak (Journal of Management Science Nakhon Pathom Rajabhat University, 2024)
The objectives of this research were to: (1) study the changes in performance of community development worker that affect the opinions of the Community Development Department and (2) create community development worker guidelines to work in the changing situation. Sample group and Key informants are 98 community development worker in the 7 province of Phetchaburi community development learning center service area. Collect qualitative data by in-depth interviews and focus group with structured items. Analyze data by content analysis. Collect quantitative data by questionnaires. Analyze data by statistics such as percentage, mean, standard deviation and enter multiple regression analysis. The results showed 1) The changes in performance of community development worker not affect to the opinions of the Community Development Department. 2) In this case, it is to adhere to the principle of working in accordance with the guidelines of “self-control, man administration and work management. (1)The principle of self-preservation in working include manage time in daily life to be balanced and always seek knowledge. (2) The principles of people domination include considerate to colleagues, teamwork and support the network and community on a regular basis. (3) The principles of occupation include patience working, aimed to achieve results through a simplify working and show the public the benefits that will be gained Including access to community leaders so that work can be smoothly driven. The recommendation from the research are study knowledge manage from community development worker best practice because community development worker operations are always add more roles, missions or change operational guidelines. Article history: Received 27 October 2022 Revised 6 November 2023 Accepted 9 November 2023 SIMILARITY INDEX = 5.94 %